THE INFLUENCE OF LIQUIDITY, LEVERAGE AND COMPANY SIZE ON MANUFACTURING COMPANY BOND RATINGS LISTED ON THE INDONESIAN STOCK EXCHANGE - Anita Erari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research is motivated by the importance of bond ratings of manufacturing companies listed on the Indonesia Stock Exchange. This research aims to determine and analyze the influence of liquidity, leverage and company size on the bond ratings of manufacturing companies listed on the Indonesian Stock Exchange. This research uses descriptive analysis and logistic regression analysis. Analysis was carried out with the help of the SPSS program. The stages in conducting hypothesis testing according to (Ghozali, 2016) are testing the feasibility of the regression model, overall model fit, and coefficient of determination (R2). Hypothesis testing includes the Partial Test (Wald Test) and Dominant Variable Test. The results of this research reveal 1) Liquidity as proxied by the current ratio (CR) has a positive and significant effect on bond ratings in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022, 2) Leverage as proxied by the debt to equity ratio (DER) has an effect insignificantly positive on the bond ratings of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022, 3) Company size calculated using the natural logarithm by looking at total assets has an insignificant negative effect on the bond ratings of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. 2019-2022, and 4) Liquidity which has a dominant influence on the bond ratings of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022.